(3GdNUGd GdecaQI ddPfhH GdebOeI hGdeDNQIs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3GdMeO ddg ZGaQ GdPfhH hEf YXeJ CeG HYO agPg CMGOjK fHhjI JJHYJgG ef cJH cKjQI HYVgG ZQjH hHYVgG eTghQ s
(3BNQgG (B:s
(3hGdbOQ Cf GdKeGfjf EPG hajJ YOJgG de JHb HGbjI efi hde JPcQ gPG BNQ GdcJGH hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG JedcGJ cKjQI CbOegG HGSe (B/ (3EHQGgje GdQHjY SfI (B1281(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs